STRATEGY FOR SOCIO-ECONOMIC DEVELOPMENT OF THE REGION - Yusupov , Nurbek; Raxmonova , Rayxona (Zamonaviy ilmiy yondashuvlar va texnologik taraqqiyotning ustuvor yo‘nalishlari, 2026)
This article examines the theoretical foundations of regional socio-economic development strategy, the factors influencing its formation, and the mechanisms for its implementation. It also highlights the role of investments, innovation, infrastructure, and human capital in ensuring sustainable regional development. The priorities and prospects of regional development are analyzed using the example of Uzbekistan.